2014
DOI: 10.1016/j.clgc.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Targeted Therapy on Overall Survival in Advanced Renal Cancer: A Study of the National Surveillance Epidemiology and End Results Registry Database

Abstract: Introduction With the advent and availability of targeted therapy, the treatment of advanced/metastatic renal cell carcinoma (RCC) underwent a drastic change in 2005. The impact of this change on clinical outcome, within the population has not been studied. The aim of this study was to evaluate the overall survival (OS), prior to, and post availability of targeted therapy, for advanced RCC cases in the population-based Surveillance, Epidemiology and End Results (SEER) cancer registry. Methods All advanced (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 19 publications
4
41
0
1
Order By: Relevance
“…We therefore postulate that a significantly larger proportion of tumors from African American patients may have a HIF-independent and VEGF-independent propensity for aggressiveness, resulting in resistance to the commonly used VEGF-targeted therapies. While our results point toward a biologic rationale for the lack of improvement in survival of African American patients since the advent of targeted therapy, 10 we recognize that there are also a host of other potential factors (eg, access to health care, time to diagnosis, and appropriate treatment) that likely contribute to the racial disparities seen in advanced ccRCC. Nonetheless, the results presented herein provide insight into the potential role that genomic variation plays in the disparity observed between races.…”
Section: Discussionmentioning
confidence: 77%
“…We therefore postulate that a significantly larger proportion of tumors from African American patients may have a HIF-independent and VEGF-independent propensity for aggressiveness, resulting in resistance to the commonly used VEGF-targeted therapies. While our results point toward a biologic rationale for the lack of improvement in survival of African American patients since the advent of targeted therapy, 10 we recognize that there are also a host of other potential factors (eg, access to health care, time to diagnosis, and appropriate treatment) that likely contribute to the racial disparities seen in advanced ccRCC. Nonetheless, the results presented herein provide insight into the potential role that genomic variation plays in the disparity observed between races.…”
Section: Discussionmentioning
confidence: 77%
“…For patients with advanced RCC in California, 3-year OS increased from 68.2% in 1998–2003 to 74.6% in 2004–2007 ( P <0.001) 19. A study based on the nationwide US Surveillance, Epidemiology and End Results (SEER) database showed a significant improvement in OS for advanced RCC patients treated after, compared with before, the introduction of targeted therapy (median OS: 15 vs 20 months; P =0.0006) 20. A recent report utilizing the 2000–2010 SEER research file indicated a significantly reduced risk for death (HR 0.86; P <0.01) among patients diagnosed with advanced RCC in the targeted therapy era compared with pre-targeted therapy era 29.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, differences in adaptation and clinical practice when introducing new therapies cannot be ascertained from RCTs, whereas data derived from national population-based registries have the potential to provide useful real-world insights into both of these issues. Although an increasing body of information supports that targeted therapy improves OS in real-world practice,1820 few studies have explored this on a national level. Comprehensive national cancer and drug prescription registries in the Nordic countries cover the whole population and, hence, provide a unique opportunity for studying the prognostic impact of new cancer medications within a real-life population and form the basis of robust real-world epidemiologic research 21,22…”
Section: Introductionmentioning
confidence: 99%
“…ABDEL-RAHMAN trials [29]. Some previous SEER analyses have evaluated the survival for pre-targeted vs. targeted therapy eras of the whole RCC population [30][31][32]. However, none of them dissected the survival changes according to histology.…”
mentioning
confidence: 99%